Errors of Omission in Outpatient Prescriptions in Jordan - Al Awawdeh, Safaa; Naddaf, Ahmad; Abuirmeileh, Amjad (Jordan Journal of Pharmaceutical Sciences, 2018)
Introduction: Prescription errors are one of the most common forms of medical errors that can occur at any pointduring drug therapy. This includes prescribing, transcribing, dispensing, administering, and monitoring. Errors ofomission in prescriptions involves the absence or incomplete specification of dosage form or strength, dose ordosage regimen and quantity or duration of drug to be supplied. Illegiblity of prescriptions and prescriptions thatviolate legal requirements are also considered errors of omission.Objectives: The aim of this study was to analyze the prescription errors in a Jordanian community pharmacysetting in order to detect the most frequent errors of omission that expose people to potential risks of medicationerrors.Methods: An audit retrospective study was conducted for screening prescriptions. 800 prescriptions wererandomly selected as a study sample. The duration of this study was 8 months and in collaboration with one oflargest chain pharmacies in Jordan. Data collection was carried out using a checklist form and later analyzed usingGraphpad prism software version 5.0.Results: Results show that the percentage of errors of omission in prescription writing related to transcriber’s andpatient information were high where errors related to prescriber’s name reached 17%, prescriber’s signature11.5%, patient name 12%, patient age 62%, patient sex 97.25% , prescription Date 16.5%, illegibility 2.75% andincomplete prescriptions 59.75%. The percentage of errors related to drug’s information errors included missingdosage form 54.75%, missing unit of strength 26.25%, missing frequency 8.5%, missing duration of treatment96.75%, unauthorized abbreviation 5%, illegible prescriptions 25.75% and incomplete prescriptions 68.25%.Conclusion: The reviewed prescriptions suffered serious deficiencies and improper writing. The findings clearlyindicate that there were asignificant errors of omission in the chosen pharmacy setting which reflects negativequality of health care.